The French Counter-radicalisation Strategy - Quivooij, Romain (2017)
Since April 2014, France has been developing a three-stage counter-radicalisation model, covering the areas of detection, prevention and de-radicalisation. Little has been said in the English literature on the organisation, the effectiveness and the challenges of this approach. France’s centralised tradition led to the implementation of a vertical structure of action dominated by the Interior Ministry. A major difficulty faced by the French authorities is to manage various “profiles” of at-risk individuals, including converts, underage individuals and young women. This illustrates a significant diversification of the groups of population affected by Salafi-Jihadist radicalisation. The French counter-radicalisation strategy is expected to lead the fight against violent extremism, but it remains hampered by divisions over the role of Islam. This bone of contention, which is indicative of the French state and society’s complex relationship with religion, substantially affects the consistency of deradicalisation programmes.